Recent advances and applications of flexible phase change composite - Lichang Lu; Hongxu Guo; Nacho Martin-Fabiani-Carrato; Ye Zhou; H Willcock; Goran Vladisavljevic; James JC Busfield; Emiliano Bilotti; Ton Peijs; Han Zhang; Yi Liu (2025)
Flexible phase change composites (FPCCs) have garnered significant attention for their ability to combine high latent heat capacity with mechanical flexibility. This combination enables advanced thermal management in emerging fields such as flexible electronics, soft robotics, and wearable technologies. Traditional phase change materials (PCMs) excel in energy absorption and release. However, their rigidity limits their applicability in the sectors above. Existing reviews largely focus on encapsulation methods and traditional PCM applications, leaving a gap in the literature concerning flexibility enhancement strategies and FPCC-specific applications. This review seeks to address this gap by presenting a comprehensive timeline of FPCC development, elucidating the principles of latent heat capacity, and systematically reviewing recent advancements in the field. Emphasis is placed on design strategies at both the structural level, such as fiber and foam configurations, and materials level, including physical blending and molecular engineering. Performance comparisons are provided, evaluating FPCCs in terms of both latent heat storage and mechanical flexibility. Furthermore, the review explores diverse applications of FPCCs in thermal energy storage, transfer, conversion, and release, underscoring their potential in cutting-edge sectors. By highlighting FPCCs' versatility and interdisciplinary applications, this review aims to inspire further research and integration of FPCCs into domains requiring both mechanical flexibility and thermal energy management solutions.